2016
DOI: 10.1002/jssc.201600220
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the pigment fraction in sweet bell peppers (Capsicum annuum L.) harvested at green and overripe yellow and red stages by offline multidimensional convergence chromatography/liquid chromatography–mass spectrometry

Abstract: Offline multidimensional supercritical fluid chromatography combined with reversed-phase liquid chromatography was employed for the carotenoid and chlorophyll characterization in different sweet bell peppers (Capsicum annuum L.) for the first time. The first dimension consisted of an Acquity HSS C18 SB (100 × 3 mm id, 1.8 μm particles) column operated with a supercritical mobile phase in an ultra-performance convergence chromatography system, whereas the second dimension was performed in reversed-phase mode wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
(25 reference statements)
3
17
0
Order By: Relevance
“…As ripening goes on, there is two possible scenarios in the yellow fruits, the accumulation of lutein and maintenance of b-carotene or the lowering of the levels of both previously cited carotenoids concomitantly with the increase in violaxanthin and a-carotene. 139,143,144,150,151 Furthermore, violaxanthin and lutein are described as the main carotenoids in ripe yellow-fruited species. 152 In species in which violaxanthin is the major carotenoid in ripe fruit, it comprises approximately 30-50% of the total content, 139 while lutein can comprises 41-67%.…”
Section: Carotenoids Modications During Ripeningmentioning
confidence: 99%
See 1 more Smart Citation
“…As ripening goes on, there is two possible scenarios in the yellow fruits, the accumulation of lutein and maintenance of b-carotene or the lowering of the levels of both previously cited carotenoids concomitantly with the increase in violaxanthin and a-carotene. 139,143,144,150,151 Furthermore, violaxanthin and lutein are described as the main carotenoids in ripe yellow-fruited species. 152 In species in which violaxanthin is the major carotenoid in ripe fruit, it comprises approximately 30-50% of the total content, 139 while lutein can comprises 41-67%.…”
Section: Carotenoids Modications During Ripeningmentioning
confidence: 99%
“…The major compounds from capsaicinoids, carotenoids and avonoids classes described during this review were used as variables to perform a Principal Component Analysis (PCA) of samples analyzed by other researchers. 64,78,127,150,156,158,160,162,176,[201][202][203][204][205] Before the PCA analysis, data were normalized to reduce the inuence of different analytical methods applied by each researcher (see ESI material †).…”
Section: Chemosystematic Perspectivementioning
confidence: 99%
“…Since then, a large number of papers was published, which emphasizes the important role of SFC as an alternative analysis technique in this sector [36]. There are different forms of carotenoids: free carotenoids and more stable forms, esterified with fatty acids [39]. To release all esters and to simplify the analysis, most of the investigations were performed after a saponification step [40].…”
Section: Carotenoidsmentioning
confidence: 99%
“…Bonaccorsi et al [39] identified more than 100 different compounds belonging to chlorophylls, free carotenes, free xanthophylls, and xanthophyll mono-and diesters in sweet bell peppers through the offline coupling of SFC and LC. The first dimension was performed on a SFC system using an Acquity UPC² HSS C 18 SB column and ethanol as modifier, while the second dimension consisted of a RP-HPLC combined with DAD and MS detection and was performed on a C30 stationary phase.…”
Section: Carotenoidsmentioning
confidence: 99%
“…Multidimensional chromatography provides enhanced resolution and separation power and an extended measured dynamic concentration range to analyze complex proteomics samples [13]. Moreover, this advantageous method offers a convenient online proteomics approach to reduce the complexity of the proteomic samples encountered during fractionation.…”
mentioning
confidence: 99%